Effect of Laughter Therapy Lowers Depression Rates In Postpartum Blues Mothers At Puskesmas Carenang - Lia Apriliana; Wintarsih Wintarsih (CV. Inara, 2023)
In June there was an average number of post partum mothers per month as many as 40 post partum mothers in the working area of the Puskesmas Carenang. Based on the results of interviews and screenings using the Edinburgh Postnatal Depression Scale (EPDS) questionnaire, out of 20 mothers, data were obtained from 13 mothers who experienced post partum blues. The purpose of this study is to determine the Effect of Laughter Therapy on Reducing Depression Rates in Post Partum Blues Mothers at the Puskesmas Carenang in 2022. This research method uses Quasi Experiment with a pre-test post test design. The samples in this study were postpartum mothers who experienced postpartum blues depression in June to July 2022 as many as 58 people, a sampling technique, namely total sampling. Data analysis using Wilcoxon test. The results showed that the average EPDS score before being given laughter therapy was 6.2. The average EPDS score after being given laughing therapy was 4.38. There is an effect of laughter therapy on decreasing postpartum depression rates (p value 0.000 <0.05). So it is hoped that this study will be able to provide education and information in overcoming postpartum blues depression conditions in post partum mothers with laughter therapy.